Automated writing evaluation tools in Business English Writing: An experimental study among Indonesian undergraduates - Binar Winantaka; Anwar Efendi; Nur Hidayanto Pancoro Setyo Putro (Universitas Ahmad Dahlan, 2026)
Business English writing competence is increasingly critical for Indonesian university graduates navigating global professional environments, yet many students continue to experience persistent difficulties with grammar, coherence, and professional register. Automated Writing Evaluation (AWE) tools such as Grammarly and Grammark provide immediate, data-driven feedback that may support writing development beyond surface-level error correction (Barrot, 2021; Calma et al., 2022). This quasi-experimental study examined whether AWE integration in a Business English writing course improved Indonesian undergraduates' perceived usefulness, ease of use, motivation, self-regulated learning (SRL), and writing self-efficacy (WSE), relative to conventional instructor feedback. Sixty undergraduate students were randomly assigned to an AWE group (n = 30) or a control group (n = 30). A validated 38-item Likert questionnaire and open-ended reflective prompts were administered post-intervention. Three key findings emerged: (1) AWE significantly enhanced perceived usefulness (d = 2.92) and ease of use (d = 2.74); (2) motivation, self-regulated learning, and writing self-efficacy increased substantially in the AWE group; and (3) students unanimously recommended a hybrid AWE–teacher feedback model to address AWE's limitations in higher-order writing development (Thi & Nikolov, 2022). These findings suggest that AWE integration holds considerable promise for Indonesian EFL Business English instruction, particularly when systematically complemented by expert human feedback.